PICTORIAL PRESENTATION AND REVIEW STRATEGIES IN SCIENCE LEARNING. - Alesandrini, Kathryn Lutz; Rigney, Joseph W. (Journal of Research in Science Teaching, 1981)
The article reports on the result of the study to test the effects of pictorial presentation and a pictorial review task on science learning in the U.S. Four conditions are presented on a computer-assisted instruction terminal and 96 undergraduate participants were randomly assigned to one of the four conditions. The effectiveness of the pictorial review task compared to a read-twice control were tested. Performance on the pictorial posttest relative to the re-read condition is facilitated by pictorial review condition.